A proton NMR study of ribosomal protein L25 from Escherichia coli. - Kime, M; Ratcliffe, R; Moore, P; Williams, R (1981)
A highly folded form of the ribosomal protein L25 from Escherichia coli can be obtained from urea-denatured preparations. Proton NMR data show that this form of the molecule must have a compact, globular tertiary structure. Spectroscopically it is indistinguishable from L25 prepared by methods which avoid denaturing solvents. Thus L25 is a protein which can be reversibly denatured. The stability and solubility of the folded form of the protein are discussed and primary assignments made for a number of resonances in its NMR spectrum. The paper shows that this folded form of the protein can be characterised using NMR spectroscopy. High-resolution NMR spectroscopy provides a sensitive and general way for the characterisation of protein folds.